Responsabilité et environnement : questionner l’usage amateur des pesticides - Julia Barrault (VertigO)
About 10000 tons of phytosanitary products (8 % of the national consumption) are spread every year in the gardens of the private individuals in France. If numerous researches were interested (and are still interested) in the agricultural manners of pesticides and in their sanitary and environmental impacts, it turns out important to question domestic uses in particular those of the amateur gardeners for several reasons: the weak surface of application, the types of treated surfaces, and the practices and the conditions of use, generate risks of pollution and sanitary risks in the same way as the agricultural manners. Besides, these manners of pesticides for the maintenance of the garden call particularly in a context marked by a strong stigmatization of these substances and a growing awareness towards the problems which they raise.But to whom falls the responsibility for preventing these risks occurring in the private sphere? To the authorities which should legislate to limit even to forbid the sale and the use? To the manufacturers who should launch on the market products more "soft"? To the distributors who should deliver quality advice or to put under key the most worrisome substances? To the gardeners who should reason with their uses and to care about their consequences?By resting as backcloth of our analysis, a society where the individual occupies a central place and where the order in an individual responsibility seems more and more marked, in particular in the environment domain, our communication will attempt to discuss, through an original research object, this notion of responsibility and the hypothesis of its new custom by the public authority which would give to see a new way of governing, more directed than previously to an individual autoregulation of the problems of environment.